New challenges and trends of administrative law in Germany - Ibler, Martin (Universidad Santo Tomás, Bogotá-Colombia, 2016)
In Germany, modern administrative law must be able to substantially contribute tothe task of overcoming national, European and global challenges. Human safety,environ-mental protection, the development of modern economies and infrastructures,as well as the protection of information, data and rights are sev-eral fieldswhere the need for continued development of administrative law is particularlyapparent. The influence of EU law and international law is evident in Germany’sreaction to these challenges, which, even with the help of its ad-ministrative law,is differentiated: Protection against threats to public safety is strengthened; otherpublic obligations are being privatized, while the state lim-its its duties to ensuringthat the private sector is fulfilling these new obligations satisfactorily. The increasedtransparency in administrative action and infor-mation law should strengthenboth environmental protection and the approval of state infrastructure planning.All objectives should be achieved without ne-glecting citizens’ rights to legal anddata protection. This will be accomplished with the support of the legislation, theadministration, the judicature and the scientific community, as German administrativelaw is based on a fundamental-ly solid rule of law and on a systematizationand legal doctrine characterized by good practice and sustainability.